Sequencing the OAS1 gene to map variation - Nalvelnathan, Janarth (2023)
Oligoadenylate synthase 1 (OAS1) has been reported to be a key player in the chance of contracting COVID-19 and in the risk of Alzheimer’s Disease. The presence of the risk Single Nucleotide Polymorphisms (SNPs) rs1131454 in the 3rd exon, resulting in a substitution of the (GG) ancestral genotype to an (AA) genotype, has been shown to have an association with both AD and COVID-19. Exonic information has been sequenced and well documented, however intronic data has not. This study aims to sequence the OAS1 introns, exons and record potential novel rare SNPs present within as well as confirmed SNPs. Using 12 individual DNA samples, 4 DNA samples with AD that were homozygous with the risk allele, 4 control samples that were homozygous with the non-risk allele, and 4 control samples that were homozygous with the risk allele, we use PCR techniques to amplify the desired OAS1 locus and sequence the amplicons using next-generation sequencing techniques (Deepseq). We identify a possible novel and known SNPs present on both exonic and intronic data of the OAS1 gene. This potentially novel SNP is located on chr12:112905116 and substitutes the T ancestral base with the C base. It was sequenced in a homozygote control sample with the non-risk allele with a Qscore of 16.64%. Rs7135577, Rs1051042 and Rs10774671, SNPs that are documented to be linked to West Nile Virus (WNV) and Tuberculosis (TB), were recorded in all risk allele samples with Qscores of over 30%, and most likely to be positive SNPs. Conclusively, our data shows a potential novel SNP on chr12:112905116 with future implications to find a potential link between it and AD, as well as multiple known SNPs that are linked to TB and WNV. Future studies can explore the risk factor and susceptibility to AD with the aforementioned SNPs.